Entrepreneurship and Change Understanding Entrepreneurialism as a Driver of Transformation - Hyams-Ssekasi, Denis; Agboma, Fredrick (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XXXII, 279 p. 18 illus.